Evaluation of Management Information Systems to Increase Palm Oil Production at PT. Cisadani Sawit Raya Tbk, Labuhanbatu - Meilianna Sri Wahyuni; Marlina Siregar; Nurintan Asyiah Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
PT. Cisadane Sawit Raya TBK. Labuhanbatu is a company engaged in the field of oil palm plantation located in Labuhanbatu district. This company is included in the company that has the most producers in the Labuhanbatu area, to increase production output, of course, a good and structured information system is needed. This study discusses the evaluation of a management information system for increasing oil palm production, a good information system is useful for planning, and making decisions about increasing oil palm production for the sustainability of the company, while the author's goal is to see what a management information system is being run by the company to improve yields palm oil production and whether the current information system is effective. The research method used is descriptive qualitative, all data that has been collected is analyzed and then a conclusion is drawn. from the results of data analysis that has been carried out, there is an increase and decrease in oil palm FFB every year, the highest production was in 2017 which increased by 17.2% from the previous year from the data that has been analyzed, it can be concluded that the management information system to increase oil palm production at PT. Cisadane Sawit Raya TBK. Labuhanbatu. This is good because the company's target is met every year, although the replanting of FFB still meets the company's target.